2020
DOI: 10.1158/1535-7163.mct-20-0369
|View full text |Cite
|
Sign up to set email alerts
|

Implication of ZNF217 in Accelerating Tumor Development and Therapeutically Targeting ZNF217-Induced PI3K–AKT Signaling for the Treatment of Metastatic Osteosarcoma

Abstract: We previously identified ZNF217 as an oncogenic driver of a subset of osteosarcomas using the Sleeping Beauty (SB) transposon system. Here, we followed up by investigating the genetic role of ZNF217 in osteosarcoma initiation and progression through the establishment of a novel genetically engineered mouse model, in vitro assays, orthotopic mouse studies, and paired these findings with preclinical studies using a small-molecule inhibitor. Throughout, we demonstrate that ZNF217 is coupled to numerous facets of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Here, we identify UM171 as a degrader of RCOR1, RCOR3, MIER2, and their associated repressor complex. Several of these proteins are candidate therapeutic targets in a wide range of life-threatening malignancies and currently lack pharmacological modulators ( 18 , 19 , 20 , 21 ). It should thus be of considerable interest to further explore the utility of UM171 as a potential therapeutic agent in these cancer settings.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we identify UM171 as a degrader of RCOR1, RCOR3, MIER2, and their associated repressor complex. Several of these proteins are candidate therapeutic targets in a wide range of life-threatening malignancies and currently lack pharmacological modulators ( 18 , 19 , 20 , 21 ). It should thus be of considerable interest to further explore the utility of UM171 as a potential therapeutic agent in these cancer settings.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the complete ZNF217 3D structure is not available [ 6 , 161 ], limiting in silico drug design. To date, the Akt inhibitor triciribine is the only drug shown to counteract the ZNF217-driven deleterious effects in vivo and has been proposed as a clinical strategy to treat ZNF217-positive cancer patients [ 10 , 119 , 162 , 163 ]. Deciphering this close interplay between ZNF217 and epigenetic processes, thus, sets the stage for considering epidrugs strategies, alone or in combination with conventional treatments, and holds potent therapeutic potential for the treatment of ZNF217-positive cancers.…”
Section: Discussionmentioning
confidence: 99%
“…This compound has been shown to decrease the survival of SH-SY5Y NB cells in both 2D and 3D culture models, affecting the migratory abilities of their sphere-forming units [ 791 ]. Triciribine demonstrated activity in EWS cell lines as well, with a mean IC50 of 24 μM, with robust synergy when combined with dasatinib; however, it did not affect tumor growth in vivo [ 792 ]. Moreover, Smeester and colleagues (2020) tested this drug in OS and showed that ATK inhibition in HOS and SJSA-1 cell lines leads to decreased cell proliferation, migration and colony capacity, and increased apoptosis.…”
Section: Kinases As Druggable Targets—evidence and Limitationsmentioning
confidence: 99%